A Performance Study on Emotion Models Detection Accuracy in a Pandemic Environment - Saravanan P.; Ravindran S.; Weng L.Y.; Mohamed Sahari K.S.B.; Anuar A.B.; Abdul Jalal M.F.B.; Mohamad Rafaai Z.F.B.; Raventhran P.N.A./P.; Mohd Radzi H.; Yussof S. (Springer Science and Business Media Deutschland GmbH, 2023)
Computers; Covid19; Deep learning; Detection accuracy; Emotion; Emotion models; Full faces; High-accuracy; Pandemic; Performance study; Skin patch; Deep learning